Mediatization by the young people in the narrative expansion of Marvel Cinematic Universe - Gosciola, Vicente (2018)
This article deals with mediatization by the young audience in narrative development and in the convergence culture and observes action as a living science in constant motion. In order to understand the factors that compose and surround the productions that are structured from this narrative paradigm, this work describes the transmedia storytelling that improves its characteristics to explain the phenomenon of the cultural presence that happens in the Marvel Cinematic Universe (MCU). In this context, we intend to apply the concepts of participatory culture, knowledge society, cultural presence and presentiment to understand how the entertainment industry, especially the MCU, reinterpreted the contemporary yearning for a new heroic narrative or epic story.